High-throughput evaluation method and system for material rolling contact performance based on fixed-period damage contrast

CN122709264APending Publication Date: 2026-09-08NCS TESTING TECHNOLOGY CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202610815929.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-06-08
Publication Date
2026-09-08

AI Technical Summary

Technical Problem

[0005]本发明的技术目的在于克服传统材料滚动接触性能评价方法效率低下的问题,提供一种新型高通量评价方法及系统

Benefits of technology

本发明提供了一种基于固定周期损伤对比的材料滚动接触性能高通量评价方法及系统,与现有技术相比,具有革命性的效率提升和极强的数据可比性。该方法的核心在于一次固定周期的实验即可平行评估数十种材料成分或状态,将传统串行模式下长达数月的研发周期缩短至天级。所有样品经历了完全相同的制备历史、热机械处理和实验工况,并在统一的预设循环次数后终止实验并进行对比,彻底消除了传统方法中因实验时序、试样状态差异及个别样品提前失效所导致的误差,使性能排序结果极为可靠。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122709264A_ABST
    Figure CN122709264A_ABST
Patent Text Reader

Abstract

The application provides a material rolling contact performance high-throughput evaluation method and system based on fixed cycle damage contrast, and belongs to the technical field of material testing. At least two different component or microstructure material samples to be tested are integrally prepared in the circumferential area of a rotating base tread, forming a multi-sample integrated wheel disc; the multi-sample integrated wheel disc is subjected to rolling contact experiment with a counter-abrasive under a set contact stress, slip rate and environmental condition for a predetermined fixed cycle number N, wherein N is a preset value, ensuring that the experiment is uniformly terminated before macroscopic complete failure occurs in any sample; at least one performance damage index of each sample under the same cycle number N is synchronously measured and obtained; and the performance damage index is used to quantitatively compare and sort the rolling contact damage resistance performance of all materials to be tested. The application shortens the traditional serial test cycle from days to hours, and establishes a direct correlation between the damage performance and the intrinsic properties of the material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of materials testing technology, specifically to a high-throughput evaluation method and system for the rolling contact performance of materials based on fixed-period damage comparison. Background Technology

[0002] This invention relates to the field of materials testing technology, specifically to methods for evaluating rolling contact wear and fatigue performance. In industries such as rail transportation, aerospace, and equipment manufacturing, the core failure mode of critical moving components such as wheels, bearings, and gears is often rolling contact fatigue and wear. Developing high-performance materials required in these fields fundamentally depends on the accurate and efficient evaluation of their wear resistance and fatigue resistance under simulated operating conditions. However, traditional testing methods, such as dual-disc or roller testing machines, typically evaluate only one material or process parameter at a time. Their sequential approach is inefficient, time-consuming, and costly. When faced with material screening tasks involving multiple components and multiple process parameters, this traditional method has become a major bottleneck restricting research and development efficiency.

[0003] While existing technologies have attempted to apply the high-throughput concept to material screening, they largely focus on tribological testing of coatings or thin films. This makes it difficult to simulate and reproduce the complex triaxial stress states and induced internal microstructure evolution experienced by bulk materials under rolling contact conditions in real engineering projects. Furthermore, traditional evaluation methods generally pursue the absolute indicator of material failure life, which is not necessary for rapid screening in the early stages of R&D. In fact, premature failure of individual samples may interrupt the entire comparative experiment, resulting in poor data comparability and failing to meet the needs for rapid, parallel comparisons.

[0004] Therefore, there is an urgent need in this field for an innovative high-throughput evaluation scheme. This scheme should overcome the aforementioned shortcomings, enabling parallel testing of multiple materials or states, rapidly obtaining a quantitative ranking of their relative damage resistance within a controllable experimental period, and effectively correlating performance differences with intrinsic material properties (such as composition and microstructure). This would provide strong data support and improve efficiency for the targeted design and development of high-performance materials. Summary of the Invention

[0005] The technical objective of this invention is to overcome the inefficiency of traditional methods for evaluating the rolling contact performance of materials, and to provide a novel high-throughput evaluation method and system. The core of this method is to prepare multiple material samples in parallel on an integrated wheel, and to subject all samples to fixed-cycle rolling contact experiments under identical conditions. By comparing their relative damage levels after the same experimental cycle, materials with superior wear resistance and fatigue resistance can be quickly and efficiently screened, thereby greatly accelerating the research and development process of new materials or processes.

[0006] To achieve the above-mentioned technical objectives of the present invention, the present invention adopts the following technical solution: A high-throughput evaluation method for the rolling contact performance of materials based on fixed-cycle damage comparison includes the following steps: S1. Multi-sample integrated preparation: At least two test material samples with different compositions or microstructures are integrated in the circumferential region of the rotating substrate tread to form a multi-sample integrated wheel; S2. Fixed-cycle rolling contact test: The multi-sample integrated wheel and the grinding part are subjected to a predetermined fixed number of rolling contact tests N under set contact stress, slip rate and environmental conditions, where N is a preset value, to ensure that the test is terminated uniformly before any of the samples undergoes complete macroscopic failure. S3. Synchronous acquisition of damage indicators: After the experiment is terminated, at least one performance damage indicator for each sample under the same number of cycles N is measured and acquired synchronously. S4. Performance Comparison and Screening: Based on the aforementioned performance damage indicators, the rolling contact damage resistance performance of all test materials is quantitatively compared and ranked.

[0007] Preferably, in step S1, the integrated fabrication includes: S11. Using directional energy deposition additive manufacturing technology, columnar or spherical material units of different compositions are formed by point-by-point cladding deposition at preset positions in the circumferential direction of the substrate surface; S12. The deposited integral disk is hot-rolled to cause all material units to undergo plastic deformation, densification, and obtain similar deformation amounts; S13. Perform uniform isothermal heat treatment on the rolled integral wheel.

[0008] Preferably, in step S2, the method for determining the fixed number of cycles N is as follows: based on empirical data of the material system or through preliminary experiments, select a number of cycles that can induce significant damage evolution but is far below the typical failure life, with a range of 10. 4 Up to 10 6 Second-rate.

[0009] Preferably, in step S3, the performance damage indicators include one or more of the following: volumetric wear amount, surface two-dimensional / three-dimensional morphology parameters, number of crack initiations, average crack length, maximum crack length, plastic deformation layer thickness, and subsurface microhardness distribution.

[0010] Preferably, while or after obtaining the tread damage index in step S3, the intrinsic material properties of the corresponding location of the flat area on the side of the multi-sample integrated wheel are characterized, including: chemical composition spectral analysis, microhardness test, microstructure observation, and electron backscatter diffraction analysis, so as to establish a mapping relationship spectrum of "composition-structure-damage performance".

[0011] Preferably, the experimental process in step S2 also includes an online cleaning step of the wheel tread surface, using non-contact high-pressure gas to tangentially blow the contact area to remove wear debris and ensure the clarity of damage observation.

[0012] To achieve the technical objective of this invention, a high-throughput evaluation system for the rolling contact performance of materials, implementing the method described in the above technical solution, is also provided, comprising: Multi-sample integrated wheel module: including a matrix and test material regions of at least two different compositions fixed to its tread circumferential direction; Double-disc rolling contact testing machine module: used to clamp and drive the disc module and the grinding wheel, and apply the set load and slip. Experimental cycle control module: electrically connected to the testing machine module, configured to automatically issue a stop command when the preset fixed number of cycles N is reached; Online cleaning module: includes gas nozzles and a pressure control system that directs air to the contact area of ​​the wheel tread surface; Multidimensional damage characterization module: including an optical / 3D topography instrument for acquiring the morphology of tread damage, and composition, hardness and microstructure analysis equipment for side material analysis; Data fusion and processing module: used to correlate and analyze data from the tread and side surfaces to generate performance comparison charts.

[0013] Preferably, the test material region in the multi-sample integrated wheel module is a metallurgical bonding region formed on the substrate by directional energy deposition additive manufacturing technology combined with subsequent hot rolling and heat treatment processes.

[0014] Preferably, the optical / 3D topography instrument in the multi-dimensional damage characterization module is configured to automatically scan the entire wheel tread after the experiment is terminated, so as to simultaneously acquire surface topography data of all test material areas.

[0015] More preferably, the data fusion and processing module is configured to align and correlate the damage index data of each material area of ​​the tread with the chemical composition and microstructure data obtained from the side characterization, and generate a visual comparison map with material composition as coordinates and damage index as visualization elements.

[0016] Compared with the prior art, the present invention achieves the following technical effects: This invention provides a high-throughput evaluation method and system for the rolling contact performance of materials based on fixed-cycle damage comparison. Compared with existing technologies, it offers revolutionary efficiency improvements and extremely strong data comparability. The core of this method lies in its ability to evaluate dozens of material compositions or states in parallel within a single fixed-cycle experiment, shortening the traditional serial R&D cycle from months to days. All samples undergo identical preparation histories, thermomechanical treatments, and experimental conditions, and the experiment is terminated and compared after a uniform preset number of cycles. This completely eliminates errors caused by differences in experimental timing, sample conditions, and premature failure of individual samples in traditional methods, making the performance ranking results extremely reliable.

[0017] This method focuses on the core screening needs in the early stages of R&D, using "damage degree under a fixed period" as the core comparison indicator to quickly and intuitively answer the engineering question of "which material is more damage-resistant," which is more economical and efficient than pursuing absolute failure life. Furthermore, this method can simultaneously acquire multi-dimensional damage information such as wear, cracks, and plastic deformation, and accurately correlate it with intrinsic properties such as chemical composition and microstructure, constructing a "composition-structure-property" mapping spectrum, providing a rich multi-dimensional data foundation for in-depth mechanism research and material design. The system design is compatible with existing standard testing machines, and by integrating online cleaning and automated characterization modules, it ensures experimental stability and the observability of results, possessing high engineering application value and intelligent closed-loop R&D potential. Attached Figure Description

[0018] For ease of explanation, the present invention will be described in detail below with reference to specific embodiments and accompanying drawings.

[0019] Figure 1 This is a flowchart of the high-throughput evaluation method for material rolling contact performance based on fixed-period damage comparison according to the present invention.

[0020] Figure 2 This is a flowchart of the radial gradient specimen preparation and fatigue testing process of the present invention. Detailed Implementation

[0021] The following are specific embodiments of the present invention, described in conjunction with the accompanying drawings, to further illustrate the technical solutions of the present invention. However, the present invention is not limited to these embodiments. Specific details, such as particular configurations, are provided in the following description merely to aid in a comprehensive understanding of the embodiments of the present invention. Therefore, those skilled in the art should understand that various changes and modifications can be made to the embodiments described herein without departing from the scope and spirit of the present invention.

[0022] It should be noted that, unless otherwise specified, the embodiments and features described in this invention can be combined with each other.

[0023] Example: Rapid screening of steel composition for high-speed train wheels From 20 wheel steel formulations with different carbon (C) and vanadium (V) contents, 1-2 candidate components with the best wear resistance and fatigue resistance were quickly screened out.

[0024] The specific steps include: 1. Ingredient Design and Layout: Based on phase diagram calculations and experience, 20 combinations of C content (0.4-0.8 wt%) and V content (0-0.2 wt%) were determined. The C content gradient was arranged along the circumference of the wheel, and the V content gradient was arranged along the axial direction. Twenty corresponding material deposition coordinate points were planned on the tread surface of the substrate wheel (45 steel).

[0025] 2. Preparation of multi-sample integrated wheel: Using a laser-guided energy deposition system, approximately spherical material units with a diameter of about 10 mm were sequentially printed at the aforementioned coordinate points. During the printing process, different metal powder compositions were switched in real time according to the design.

[0026] After printing, the entire disc is hot-rolled at 1100°C, with a total deformation of approximately 50%. This step aims to densify and flatten all printed spherical units and achieve similar amounts of plastic deformation.

[0027] The hot-rolled integral wheel is subjected to uniform isothermal heat treatment, specifically isothermal treatment at 560°C for 1 hour followed by air cooling to room temperature.

[0028] 3. Fixed-period rolling contact test: The prepared integrated wheel is installed on the upper spindle of the double-disc testing machine, and the grinding wheel made of standard steel rail material is installed on the lower spindle.

[0029] The experimental parameters were set as follows: contact stress 1200 MPa, slip rate 0.5%, simulating linear running conditions, and the environment was dry air at room temperature.

[0030] Key setting: Preset fixed number of loops N = 5 × 10 5 The testing machine's control module automatically shuts down when this number of cycles is reached. This number of cycles is designed to induce significant damage but is well below the typical failure life.

[0031] During the experiment, the online cleaning module was activated, using clean compressed air at 0.3 MPa to continuously blow through a nozzle at a 30° tangential angle to the contact area to remove wear debris, ensuring experimental stability and clarity of subsequent observations.

[0032] 4. Simultaneous acquisition of damage indicators: After the experiment was stopped, a three-dimensional white light interferometer was used to automatically scan the entire wheel tread surface to obtain the three-dimensional morphology of each material region. The volumetric wear and root mean square surface roughness Sq of each region were automatically calculated by software.

[0033] Using a high-definition optical microscope and image analysis software, the number of cracks per unit area in each material region was counted, and the length of the maximum crack was measured.

[0034] 5. Representation of intrinsic attribute associations: Remove the wheel and perform precision wire cutting and polishing on its side (axial section).

[0035] A spark spectrometer was used to scan along the circumference of the side to obtain a precise chemical composition distribution curve, which was then correlated with the coordinates of the printed design.

[0036] Vickers hardness tests and SEM / EBSD observations were performed at corresponding locations in each material area on the side to obtain information on hardness distribution and microstructure (such as pearlite lamellar spacing, pearlite cluster diameter, inclusion type and size).

[0037] 6. Data fusion and performance ranking: The data fusion module precisely aligns the "position coordinates" of 20 material zones on the tread with the "composition-organism coordinates" on the side.

[0038] A comprehensive performance comparison chart was generated. The chart uses C content as the X-axis and V content as the Y-axis, with color intensity representing volumetric wear and bubble size representing the maximum crack length. The chart visually shows that the area corresponding to component A (C: 0.6%, V: 0.1%) has the lightest color (minimum wear) and the smallest bubbles (shortest crack), indicating that it has the best overall damage resistance performance.

[0039] Meanwhile, the data revealed the interaction between C and V elements: the hardness of the high carbon region is generally higher, but the crack sensitivity is also increased, while the addition of vanadium can effectively inhibit crack propagation at medium carbon content.

[0040] Those skilled in the art to which this application pertains may modify or supplement the specific embodiments described or use similar methods to replace them, but without departing from the inventive concept of this application or exceeding the scope defined by the appended claims.

Claims

1. A high-throughput evaluation method for the rolling contact performance of materials based on fixed-period damage comparison, characterized in that, Includes the following steps: S1. Multi-sample integrated preparation: At least two test material samples with different compositions or microstructures are integrated in the circumferential region of the rotating substrate tread to form a multi-sample integrated wheel; S2. Fixed-cycle rolling contact test: The multi-sample integrated wheel and the grinding part are subjected to a predetermined fixed number of rolling contact tests N under set contact stress, slip rate and environmental conditions, where N is a preset value, to ensure that the test is terminated uniformly before any of the samples undergoes complete macroscopic failure. S3. Synchronous acquisition of damage indicators: After the experiment is terminated, at least one performance damage indicator for each sample under the same number of cycles N is measured and acquired synchronously. S4. Performance Comparison and Screening: Based on the aforementioned performance damage indicators, the rolling contact damage resistance performance of all test materials is quantitatively compared and ranked.

2. The method according to claim 1, characterized in that, In step S1, the integrated fabrication includes: S11. Using directional energy deposition additive manufacturing technology, columnar or spherical material units of different compositions are formed by point-by-point cladding deposition at preset positions in the circumferential direction of the substrate surface; S12. The deposited integral disk is hot-rolled to cause all material units to undergo plastic deformation, densification, and obtain similar deformation amounts; S13. Perform uniform isothermal heat treatment on the rolled integral wheel.

3. The method according to claim 1, characterized in that, In step S2, the method for determining the fixed number of cycles N is as follows: based on empirical data of the material system or through preliminary experiments, select a number of cycles that can induce significant damage evolution but is far below the typical failure life, with a range of 10. 4 Up to 10 6 Second-rate.

4. The method according to claim 1, characterized in that, In step S3, the performance damage indicators include one or more of the following: volumetric wear amount, surface two-dimensional / three-dimensional morphology parameters, number of crack initiations, average crack length, maximum crack length, plastic deformation layer thickness, and subsurface microhardness distribution.

5. The method according to claim 1, characterized in that, While or after obtaining the tread damage index in step S3, the intrinsic material properties of the corresponding locations on the flat side area of ​​the multi-sample integrated wheel are characterized, including: chemical composition spectral analysis, microhardness testing, microstructure observation, and electron backscatter diffraction analysis.

6. The method according to claim 1, characterized in that, The experiment in step S2 also includes an online cleaning step for the wheel tread surface, using non-contact high-pressure gas to tangentially blow the contact area to remove wear debris and ensure the clarity of damage observation.

7. A high-throughput evaluation system for the rolling contact performance of materials that implements the method of any one of claims 1-6, characterized in that, include: Multi-sample integrated wheel module: including a matrix and test material regions of at least two different compositions fixed to its tread circumferential direction; Double-disc rolling contact testing machine module: used to clamp and drive the disc module and the grinding wheel, and apply the set load and slip. Experimental cycle control module: electrically connected to the testing machine module, configured to automatically issue a stop command when the preset fixed number of cycles N is reached; Online cleaning module: includes gas nozzles and a pressure control system that directs air to the contact area of ​​the wheel tread surface; Multidimensional damage characterization module: including an optical / 3D topography instrument for acquiring the morphology of tread damage, and composition, hardness and microstructure analysis equipment for side material analysis; Data fusion and processing module: used to correlate and analyze data from the tread and side surfaces to generate performance comparison charts.

8. The system according to claim 7, characterized in that, The test material region in the multi-sample integrated wheel module is a metallurgical bonding region formed on the substrate by directional energy deposition additive manufacturing technology combined with subsequent hot rolling and heat treatment processes.

9. The system according to claim 7, characterized in that, The optical / 3D topography instrument in the multi-dimensional damage characterization module is configured to automatically scan the entire wheel tread after the experiment is terminated, so as to simultaneously acquire the surface topography data of all test material areas.

10. The system according to claim 7, characterized in that, The data fusion and processing module is configured to align and correlate the damage index data of each material area of ​​the tread with the chemical composition and microstructure data obtained from the side characterization, and generate a visual comparison map with material composition as coordinates and damage index as visualization elements.